Cultura organizacional e desempenho dos colaboradores :um estudo exploratório no setor hoteleiro - Câmara, Ana Rosa Gouveia Sobral da (2006)
This work focuses on the relationship between organizational culture and quality culture in the hotel sector of NATAL/RN with respect to employee performance. The themes organizational culture and quality have been the research focus of administration theorists and a constant concern of professional managers, since the Japanese demonstrated effective forms or western management. In this study, the Competing Values Model (C.V.M.) (Quinn e Cameron, 1996; Quinn, 1998; Santos, 1998, 2000; Teixeira, 2001), which was tested on north-American organizations and considered a high value academic and professional instrument, was applied. The model maps the organizational culture on a profile with four elements: clan, adhocracy, market and hierarchy. The C.V.M., associated with the taximetrics created by Cameron (which classifies quality culture in for levels: status quo, error detection, error prevention and perpetual creative quality) has been related with organizational performance. In this study, these two models are used jointly and tested in the hotel sector. The results indicate that the strongest element of the profile is clan, which is characterized by internal focus, participation and people involvement, followed by the adhocracy element, which has an external focus, emphasizes flexibility and is characterized by dynamic enterprising and creativity. Regarding the level of the culture s quality in the hotel, the highest level, that of perpetual improvement and creativity, which attempts to enchant and to surprise the clients, was most frequently cited, followed by the error detection level, which has as its goal to discover and correct mistakes, trying, consequently, to reduce waste. The results suggest that employee performance as measured on some indicators is related to elements of the organizational culture profile and quality level